Where latest advances in HIV are shared: 21st Bangkok International Symposium on HIV Medicine. (4th March 2019) - Ohata, Pirapon June; Han, Win Min; Colby, Donn; Kerr, Stephen; Avihingsanon, Anchalee; Puthanakit, Thanyawee; Phanuphak, Nittaya; Seekaew, Pich; Ubolyam, Sasiwimol; Gatechompol, Sivaporn; Kroon, Eugene; Nanthapisal, Kesdao; et al.
Bangkok International Symposium on HIV Medicine is the largest regional conference on clinical HIV medicine in Southeast Asia. Held annually during the third week of January and spanning 3 days, the symposium provides updates on HIV and co-infection treatment and prevention. It is sponsored by HIV Netherlands Australia Thailand Research Collaboration (HIV-NAT), the first and largest clinical research center in Thailand and region. HIV-NAT was founded by the late David Cooper, late Joep Lange and Emeritus Praphan Phanuphak, who dedicated their lives to making HIV care and treatment accessible to people living with HIV in Thailand and throughout the developing world. The symposium continues its tradition of bringing the latest information in the field of HIV medicine to healthcare professionals.